Genome-wide identification and co-expression network analysis of Aux/IAA gene family in Salvia miltiorrhiza - Bin Huang; Yuxin Qi; Xueshuang Huang; Peng Yang (PeerJ, 2023)
The auxin/indole-3-acetic acid (Aux/IAA) gene family serves as a principal group of genes responsible for modulating plant growth and development through the auxin signaling pathway. Despite the significance of this gene family, the identification and characterization of members within the well-known Chinese medicinal herb Salvia miltiorrhiza (S. miltiorrhiza) have not been thoroughly investigated. In this study, we employed bioinformatics methods to identify 23 Aux/IAA genes within the genome of S. miltiorrhiza. These genes were classified into typical IAA and atypical IAA based on their domain structure. Our analysis of the promoter regions revealed that the expression of these genes is regulated not only by auxins, but also by other hormones and environmental factors. Furthermore, we found that the expression patterns of these genes varied across various tissues of S. miltiorrhiza. While our initial hypothesis suggested that the primary function of these genes was the interaction between SmIAA and ARF, gene co-expression network analysis revealed that they are also influenced by various other transcription factors, such as WRKY and ERF. The findings establish a sturdy basis for future investigations into the function of the Aux/IAA gene family and exhibit promising prospects for enhancing the genetics of this medicinal flora and its associated species.